PEMIKIRAN EKONOMI ISLAM INDONESIA STUDI PEMIKIRAN CENDEKIAWAN MUSLIM INDONESIA ERA PRA-KEMERDEKAAN – ORDE BARU - fasya, fasya (Al - Muamalat, 2017)
This study is the result of literature review on Islamic economic thought in Indonesia. This research is a qualitative research and aims to compare the Islamic economic thought in Indonesia. Historical studies are needed to construct the different. This study will divided the thought into three periods with one strong figure in each; H.O.S Tjokroaminoto which represents the pre-independence era, Sjafruddin Prawiranegara for Old Order era, and A.M Saefuddin represents the New Order era. This research will only focus on three theme of discussion: ownership, riba and interest, and zakah. In conclution, there are difference between each figure in term of epistemology and axiology level.